Study on supercritical water regeneration of bio-based activated carbon saturated with acid red G - Yaling Mu; Zitong Zhuang; Kun Jiang; Yimeng Wei; Anjun Meng; Hui Jin (Carbon Resources Conversion)
The dye and textile industry commonly employs activated carbon adsorption technology due to its cost-effectiveness and high efficiency. However, disposing of waste-activated carbon has a significant environmental and human health impact, and it’s a huge economic waste. This study investigates the kinetic and isothermal adsorption characteristics of Acid Red G dye adsorption by Powdered Activated Carbon derived from coconut shells. To effectively reuse activated carbon and maximise resource conservation, regeneration experiments were carried out using Supercritical Water at 24 MPa and 400 ℃ for 30 min. The experimental results demonstrated that, in comparison with thermal regeneration, supercritical water possesses the benefits of environmental protection, economic efficiency and extensive applicability. This is of considerable importance to the field of research concerning the regeneration of activated carbon.